2013
DOI: 10.1254/jphs.13037fp
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Studies of Four Major Phytochemical Components of Da-Cheng-Qi Decoction to Treat Acute Pancreatitis

Abstract: Abstract. The medicinal herb formulation Da-Cheng-Qi decoction (DCQD) has been shown to ameliorate the severity of acute pancreatitis by regulating an apoptosis-necrosis switch in cells. The active components responsible for this effect and their detailed mechanism of action remain unclear. Here we determine the pharmacokinetic characteristics of the four most abundant compounds in DCQD using a rat model of severe acute pancreatitis. Acute pancreatitis-like symptoms were first induced in rats and then they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…We identified ten components in serum after oral administration of a single dose of DCQD in rats [15]. Some of these components exert anti-inflammatory effects [11], including rhein, magnolol, hesperidin, and naringin, each of which might contribute to regulation of a necrosis-apoptosis switch by DCQD. These findings suggest that rhein is one of the most bioactive components of DCQD [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified ten components in serum after oral administration of a single dose of DCQD in rats [15]. Some of these components exert anti-inflammatory effects [11], including rhein, magnolol, hesperidin, and naringin, each of which might contribute to regulation of a necrosis-apoptosis switch by DCQD. These findings suggest that rhein is one of the most bioactive components of DCQD [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these components exert anti-inflammatory effects [11], including rhein, magnolol, hesperidin, and naringin, each of which might contribute to regulation of a necrosis-apoptosis switch by DCQD. These findings suggest that rhein is one of the most bioactive components of DCQD [11]. Therefore, we investigated the effects of rhein in an attempt to identify the bioactive components of DCQD that underlie its ability to modulate a necrosis-apoptosis switch and thereby alleviate the severity of AP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combinations of traditional Chinese and Western treatments are more comprehensive and effective for relieving symptoms than western medicine alone by controlling the course of the disease and reducing mortality [12]. Many studies have investigated the mechanisms of action of various decoctions for the treatment of SAP [13, 14]. Our previous studies found that DCQD significantly improves pathological pancreatic damage in a mouse model of acute necrotizing pancreatitis, inhibits inflammatory reactions, alleviates capillary leakage, and eases the symptoms of SAP-complicated SIRS [15].…”
Section: Introductionmentioning
confidence: 99%